AN ANALYSIS OF LOCUTIONARY SPEECH ACT OF ANTAGONIST MAIN CHARACTER IN THE BAD SEED MOVIE BY ROB LOWE - Satria Yanti; Irfan Hamonangan Tarihoran (GLOBAL: Education Language and Humanity Journal, 2024)
This study aims to describe the forms of locutionary speech acts used by the main antagonist in “The Bad Seed” movie and the components that influence the speech acts used by the antagonist main character. This research uses a qualitative method with a descriptive approach. Then, the data source in this study is “The Bad Seed” movie. This research focuses on the forms of locutionary speech acts and the components influencing the speech acts used by the main antagonist in “The Bad Seed” movie. Meanwhile, data collection techniques are documentation, observation, and transcription. Then, data analysis techniques are data reduction, data display, and conclusion drawing or verifying. The results showed two findings. Firstly, the total number of utterances of the main antagonist in “The Bad Seed” movie is 179 utterances, with the following division: declarative utterances are 101 (66.9%) utterances, interrogative 39 (25.8%) and imperatives are 11 (7.3 %). %) speech. From the three forms of locutionary speech acts used by the main antagonist in “The Bad Seed” movie, the declarative form is the most widely used and the imperative form is the least used by the antagonist main character in his conversation. Secondly, the components behind the speech acts of the main antagonist are setting and scene, participants, ends, action sequences, key, instrumentalities, norms of interaction, and genre